Design of dual band notched ultra wideband microstrip patch antenna for 5G lower bands application - Mahfuz, M. M. Hasan; Islam, Md. Rafiqul; Abdul Malek, Norun; Islam, Md. Shazzadul; Asadullah, G. M. (2020)
Fifth-generation (5G) forums in ASEAN countries have proposed lower frequency bands for 5G applications at 4.5 – 5.5 GHz and also the fixed-satellite service (FSS) has realised 3.3 – 3.8 GHz in C-band for 5G cellular communication recently, which leads the necessity of proposing antennas for the particular bands. In this paper, a compact ultra-wideband (UWB) patch antenna with dual band-notched characteristics has been proposed for lower 5G bands. The UWB has been achieved with a partial ground plane and further two notched 5G bands have been obtained with a rectangular slot on the patch and by connecting an arc shape open loop (ASOL) on top of the patch. The antenna has achieved a wide – 10 dB bandwidth of around 12.4 GHz (2.91 – 15.3 GHz) and VSWR < 2 except for two notched lower 5G bands of 3.3 – 4.2 GHz and 4.5 – 5.5 GHz. Besides, the proposed antenna has achieved a peak radiation efficiency of more than 80 % for UWB, while, at the notched bands as low as 40%. Moreover, the proposed antenna is compact with a dimension of 29×23 mm2 that makes it suitable for lower 5G bands application.